On the compactness of the set of L-2 trajectories of the control system - Huseyin, Nesir; Huseyin, Anar (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, the compactness of the set of L2 trajectories of the control system described by the Urysohn-type integral equation is studied. The control functions are chosen from the closed ball of the space L2 with radius r and centered at the origin. Existence of an optimal trajectory of the optimal control problem with lower semicontinuous payoff functional is discussed.